2013
DOI: 10.1186/1556-276x-8-490
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of idealized folded carbyne loops

Abstract: Self-unfolding items provide a practical convenience, wherein ring-like frames are contorted into a state of equilibrium and subsequently  pop up’ or deploy when perturbed from a folded structure. Can the same process be exploited at the molecular scale? At the limiting scale is a closed chain of single atoms, used here to investigate the limits of stability of such folded ring structures via full atomistic molecular dynamics. Carbyne is a one-dimensional carbon allotrope composed of sp-hybridized carbon atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…The recent reported results [1] as well as continued work with carbyne systems [6] motivated a confirmation of our results, as well as the validity of ReaxFF for use for carbyne. We report here a numerical error discovered in our original work -not in the ReaxFF potential, but rather a bug in the averaging algorithm implemented in the MD software package LAMMPS [7].…”
supporting
confidence: 84%
“…The recent reported results [1] as well as continued work with carbyne systems [6] motivated a confirmation of our results, as well as the validity of ReaxFF for use for carbyne. We report here a numerical error discovered in our original work -not in the ReaxFF potential, but rather a bug in the averaging algorithm implemented in the MD software package LAMMPS [7].…”
supporting
confidence: 84%
“…ReaxFF CHO can accurately provide the chemical reaction process of dehydrogenation, for example, from H 3 C–CH 2 –CH 2 –CH 3 to HCC–CCH . It has also been demonstrated that the ReaxFF potential provides a reasonable account of the chemical and mechanical behavior of many carbon-based materials, including carbyne . The velocity Verlet algorithm is employed to integrate Newton’s equations of atom motion numerically with a time step of 0.1 fs.…”
Section: Methodsmentioning
confidence: 99%
“…Several chemical methods were proposed for synthesizing stable finite-length carbon chains [4][5][6][7]. The intense interest in studying the structure and mechanics of carbyne [8][9][10][11][12][13], besides experimental efforts for fabricating carbyne chains with different lengths is because of its novel electron transport mechanism, possible applications as graphene interconnectors [14], its prospect of being used as a component in atomistic scale circuits [9,10], and also other possible technological breakthroughs.…”
Section: Introductionmentioning
confidence: 99%